Automatic term extraction based on feature combination - Lukashevich, N.V.; Logachev, Yu.M. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2010)
The paper describes the method of extraction of two-word domain terms combining their features. The features are computed from three sources: the word usage statistics in a domain-specific text collection, the statistics of global search engines, and a domain-specific thesaurus. The evaluation of the approach is based on the terminology from Ontology on natural sciences and technology. We show that the use of multiple features considerably improves the automatic extraction of domain-specific terms.